Implications of Diabetes-Induced Altered Metabolites on Retinal Neurodegeneration - Aldosari, Dalia I.; Malik, Ajamaluddin; Alhomida, Abdullah S.; Ola, Mohammad S. (Frontiers in Neuroscience, 2022)
Diabetic retinopathy (DR) is one of the major complications of diabetic eye diseases, causing vision loss and blindness worldwide. The concept of diabetic retinopathy has evolved from microvascular disease into more complex neurovascular disorders. Early in the disease progression of diabetes, the neuronal and glial cells are compromised before any microvascular abnormalities clinically detected by the ophthalmoscopic examination. This implies understanding the pathophysiological mechanisms at the early stage of disease progression especially due to diabetes-induced metabolic alterations to damage the neural retina so that early intervention and treatments options can be identified to prevent and inhibit the progression of DR. Hyperglycemia has been widely considered the major contributor to the progression of the retinal damage, even though tight control of glucose does not seem to have a bigger effect on the incidence or progression of retinal damage that leads to DR. Emerging evidence suggests that besides diabetes-induced hyperglycemia, dyslipidemia and amino acid defects might be a major contributor to the progression of early neurovascular retinal damage. In this review, we have discussed recent advances in the alterations of key metabolites of carbohydrate, lipid, and amino acids and their implications for neurovascular damage in DR.